Numerical and experimental procedure for material calibration using the serial/parallel mixing theory, to analyze different composite failure modes. Issue 14 (23rd June 2021) - Granados, Joel Jurado; Martinez, Xavier; Nash, Niamh; Bachour, Carlos; Manolakis, Ioannis; Comer, Anthony; Di Capua, Daniel
Abstract: This work proposes a calibration procedure to obtain the material parameters required by the Serial/Parallel Mixing Theory for the analysis of composites. A set of experimental tests are defined to obtain the main composite failure modes. Then, it is proposed to calculate the parameters required by the formulation using the experimental results. The procedure proposed is validated by comparing the numerical results, with those obtained from the experimental campaign. This comparison shows that the Serial/Parallel mixing theory is capable of representing the failure modes of the composite for different loading scenarios as well as the material toughness.